Neural Correlates of Audiovisual Temporal Binding Window in Individuals With Schizotypal and Autistic Traits: Evidence From Resting‐State Functional Connectivity. Issue 4 (14th December 2020) - Zhou, Han‐yu; Wang, Yong‐ming; Zhang, Rui‐ting; Cheung, Eric F. C.; Pantelis, Christos; Chan, Raymond C. K.
Abstract: Temporal proximity is an important clue for multisensory integration. Previous evidence indicates that individuals with autism and schizophrenia are more likely to integrate multisensory inputs over a longer temporal binding window (TBW). However, whether such deficits in audiovisual temporal integration extend to subclinical populations with high schizotypal and autistic traits are unclear. Using audiovisual simultaneity judgment (SJ) tasks for nonspeech and speech stimuli, our results suggested that the width of the audiovisual TBW was not significantly correlated with self‐reported schizotypal and autistic traits in a group of young adults. Functional magnetic resonance imaging (fMRI) resting‐state activity was also acquired to explore the neural correlates underlying inter‐individual variability of TBW width. Across the entire sample, stronger resting‐state functional connectivity (rsFC) between the left superior temporal cortex and the left precuneus, and weaker rsFC between the left cerebellum and the right dorsal lateral prefrontal cortex were correlated with a narrower TBW for speech stimuli. Meanwhile, stronger rsFC between the left anterior superior temporal gyrus and the right inferior temporal gyrus was correlated with a wider audiovisual TBW for non‐speech stimuli. The TBW‐related rsFC was not affected by levels of subclinical traits. In conclusion, this study indicates that audiovisual temporal processing may not be affected by autistic and schizotypal traits and rsFC between brain regions responding to multisensory information and timing may account for the inter‐individual difference in TBW width. Lay summary: Individuals with ASD and schizophrenia are more likely to perceive asynchronous auditory and visual events as occurring simultaneously even if they are well separated in time. We investigated whether similar difficulties in audiovisual temporal processing were present in subclinical populations with high autistic and schizotypal traits. We found that the ability to detect audiovisual asynchrony was not affected by different levels of autistic and schizotypal traits. We also found that connectivity of some brain regions engaging in multisensory and timing tasks might explain an individual's tendency to bind multisensory information within a wide or narrow time window. Autism Res 2021, 14: 668–680 . © 2020 International Society for Autism Research and Wiley Periodicals LLC